Assessment on the Programs and Implementation of Health Services in the University - Edmelyn B. Cacayan; Angelito E. Alvarado; Kennedy M. Pelico; Ruby Joy M. Pelico; Trisha Mae B. Ocampo; Rushel F. Samut; Maureen May B. Pascua (Humanistic Network for Science and Technology (HNST), 2021)
The highly provision of good and quality health care services is indeed a highly difficult challenge to take. The density of implementation of health service entails a mass involvement to alleviate the development it needs to sustain quality and effectivity to various phenomenal issues or situations. However, to coagulate a health care services it needs some improvements especially that the situation is being modernize and develop by various innovations and researches that therefore be inoculated to the system and be applied to the environment for better implementation and utilization. Nevertheless, the catalytic changes would be much better need today’s situations and that would be input thru comprehensively decisions and assessments. This study aimed to assess the programs and health services, and implementation of health services in terms of accessibility, provider, and quality of the University Health Services. Qualitative descriptive survey was conducted on 111 respondents to assess the level of attainment on the programs and health services, and level of satisfaction on the implementation of health services in terms of accessibility, provider and quality. For the respondent probability sampling and purposive sampling were used in because not all the population will be the respondents. Data were collected and analysed by frequency count and weighted mean. The result were the programs and health services were marked as attained which being rated by the respondents, while in terms of the dimension variable it is enlightening that the satisfaction level on the accessibility, provider and quality of health services marked as satisfy as evidence on the average weighted mean. The study concluded that in order to fully attain the programs and health services it needs to be intensify comprehensively and more strengthen regarding on the implementation of the health services and its programs. The action would augment the effectiveness of the health programs by putting it into more comprehensive health services and programs for long term implementation. Moreover, it will guarantee the health of the university at the same time to the faculty and staff including the students within the university. The dimension variable of satisfaction level on the accessibility, provider and quality of health services marked as satisfy as evidence on the average weighted mean. The implication is that health services and programs needs to heighten and be more utilize in the university exclusively to the individual to attain its optimum satisfaction level. Moreover, to alleviate the access to quality care and strengthen health care provider’s ability to plan, coordinate and manage services. This intervention would sustain its functionality and purpose for continuum of care. Keywords: assessment; programs; implementation; health services; satisfaction